Uji Formulasi Pupuk Hayati Padat Berbasis Azolla Terhadap Populasi dan Fungsional Mikroba Tanah Menguntungkan - Mieke Rochimi Setiawati; Maya Damayanti; Diyan Herdiyantoro; Pujawati Suryatmana; Fiqriah Hanum Khumairah (Soilrens, 2017)
Inorganic fertilizer is a very important agricultural input to increase agricultural production. Uncalculated and continuous application of inorganic fertilizers will lead to the reduction of soil fertility and degradation of environmental quality. Therefore, a strategy is needed to support the environmental sustainability in agriculture. One of the efforts is through the production of biofertilizer and organic fertilizer from local resources. Organic fertilizer for rice plants can be made by utilizing the local water fern, Azolla pinnata. A. pinnata can be applied on rice fields as green manure by directly placing it into the soil or spread on the surface of rice fields. Organic fertilizer that made from Azolla will be more advantageous because it can be applied with biofertilizer. This study aimed to determine the formulation of Azolla based solid biofertilizer that can support the growth of functional microbial population based on the Agriculture Ministry (Permentan) standard number 70/2011. The design of the study method used was Completely Randomized Design with six replications. The treatments used were inoculant starter with 3% molasses, 3% molasses + 10% rice wash water, 3% molasses + 1% yeast extract, and 3% molasses + 10% rice wash water + 1% yeast extract. The results of this study showed that Azolla-based solids fertilizer with starter formula 3% inoculant molasses + 10% rice water + 1% yeast extract have the population of Azotobacter, Azospirillum, endophytic bacteria and phosphate solubilizing microbe were greater than 108 cfu/g dry weight. Functional microbial of solids fertilizers in all formulas used do not show the difference on inhabiting in the N-free media or Pikovskaya selective media.  Keywords: Azolla pinnata, formulation, biofertilizer, organic fertilize